2019
DOI: 10.12681/mms.18102
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive interactions between juvenile swordfishes and blue sharks in the Western Mediterranean: a widespread phenomenon?

Abstract: There are numerous reports of billfishes spearing objects, marine organisms, and even humans. Whether or not this behaviour is intentional and, if so, what is its functional meaning, are open questions. In 2016, an adult blue shark (Prionace glauca) was found to be killed by a juvenile swordfish (Xiphias gladius) in the western Mediterranean. Here we report on three more recent cases involving both species in the same area. In February 2017, an adult male blue shark was found stranded in Garrucha (Spain) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Clear proof of an interaction of a blue shark with two swordfish is reported for the first time in this paper (finding of two bill fragments impaled in the head of the shark), although Penadés-Suay et al (2019) hypothesized a similar event in a blue shark stranded on the beach of Vera (Spain). Indeed, these authors found a swordfish bill fragment inside the right nostril, referred to an old injury, and then to a previous not deadly interaction with the blue shark, but also a mortal wound anteriorly to the right eye, without an associated bill fragment and possibly related to another swordfish attack (Penadés-Suay et al, 2019). All swordfish attacks against blue sharks reported in the literature (see Appendix 1) seem to reveal a precise defensive strategy performed by juvenile swordfish, which aims to hit the shark by targeting the head region where vital organs are located.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Clear proof of an interaction of a blue shark with two swordfish is reported for the first time in this paper (finding of two bill fragments impaled in the head of the shark), although Penadés-Suay et al (2019) hypothesized a similar event in a blue shark stranded on the beach of Vera (Spain). Indeed, these authors found a swordfish bill fragment inside the right nostril, referred to an old injury, and then to a previous not deadly interaction with the blue shark, but also a mortal wound anteriorly to the right eye, without an associated bill fragment and possibly related to another swordfish attack (Penadés-Suay et al, 2019). All swordfish attacks against blue sharks reported in the literature (see Appendix 1) seem to reveal a precise defensive strategy performed by juvenile swordfish, which aims to hit the shark by targeting the head region where vital organs are located.…”
Section: Discussionmentioning
confidence: 99%
“…The size and proportions of the bill fragments indicated that the perpetrators of these swordfish attacks were juvenile individuals, similarly to the other recent cases of swordfish attacks against the blue shark reported by Penadés-Suay et al . (2017, 2019). These authors firstly examined a large blue shark stranded on the Mediterranean Spanish coast of Valencia in September 2016 (Penadés-Suay et al ., 2017), and then reported four other cases of similar interactions (Penadés-Suay et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations